ANALYZING THE RHETORICAL STRATEGIES OF MARTIN LUTHER KING JR (Modern education and development, 2024)
This article explores the rhetorical strategies employed by Martin Luther King Jr. in his speeches, particularly his use of language to inspire social change, unify audiences, and advocate for civil rights. By analyzing key speeches, such as the "I Have a Dream" speech and the "Letter from Birmingham Jail," the article reveals how King’s rhetoric was shaped by his deep understanding of his audience and his ability to use persuasive techniques to convey messages of justice, equality, and nonviolent resistance.